The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
A.L. Korkin – General principles, features of developmentand course of gallstone disease on a background of opisthorchiasis.M.V. Bundina – Outcomes of liver cirrhoses of various etiology.